Approximation to the pathology and causes of death of stranded cetaceans in the southwestern coast of spain (2001 - 2005) - De La Fuente Marquez,Jesus; Carrasco, Librado; Arbelo Hernández, Manuel Antonio; Fernández Rodríguez, Antonio Jesús (2011)
In order to establish an approximation to the pathology and causes of death of existing species in the southwest coast of Andalusia (Spain), forty-seven stranded cetaceans were studied between 2001 and 2005. The animals recovered were: fifteen common dolphins (Delphinus delphis), eight striped dolphins (Stenella coeruleoalba), seven bottlenose dolphins (Tursiops truncatus), six minke whales (Balaenoptera acutorostrata), five harbour porpoises (Phocoena phocoena), two fin whales (Balaenoptera physalus), one long-finned pilot whale (Globicephala melas) and three more delphinids that could not be identified. The study was performed using a systematic standardized necropsy and histopathological protocol. Because of the decomposition status of the carcasses, a complete or partial necropsy was done to twenty-eight animals (59.57%), and samples were collected from twenty-three of them (48.94%) for its histopathological study. Causes of death (defined as pathological entities) of twenty-six animals (55.32%) could be diagnosed. Most of the necropsied cetaceans (84.62%) were diagnosed as natural pathological entities that included consumptive (46.15%), non consumptive (23.08%) and neonatal/perinatal (15.38%) pathologies. The remaining animals were diagnosed as anthropogenic origin pathological entities (15.38%) that included fishing interaction (11.54%) and ship collisions (3.84%). The most frequently observed lesions were those related to infectious diseases, active stranding and advanced age of animals. This study supports the usefulness of pathological studies in stranded animals for health population management.